2001
DOI: 10.1002/jnr.1240
|View full text |Cite
|
Sign up to set email alerts
|

Density dependent modulation of cell cycle protein expression in astrocytes

Abstract: The proliferation of type-1 astrocytes is strongly inhibited by homotypic cell-contact. To examine the mechanisms mediating this inhibition of proliferation, the expression of cell cycle related proteins was compared between exponential growth-phase and contact-inhibited astrocytes. Expression of the cyclin-dependent kinase (Cdk) inhibitor p27Kip1 was upregulated 10-fold in confluent compared with growth-phase cultures. Density-induced expression of p27Kip1 was reversible. When confluent cultures of astrocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 54 publications
2
41
1
Order By: Relevance
“…Furthermore, the normal increase in the number of EGFP-negative existing (normal) astrocytes seen in the Ctr neocortex between P4 and P21 did not occur in the Cko neocortex. As astrocytes are known to occupy non-overlapping territories (Bushong et al, 2002), there may be a contact-dependent mechanism that regulates their density (Nakatsuji and Miller, 2001).…”
Section: Competition Between the Ng2 Cell-derived Astrocytes And Exismentioning
confidence: 99%
“…Furthermore, the normal increase in the number of EGFP-negative existing (normal) astrocytes seen in the Ctr neocortex between P4 and P21 did not occur in the Cko neocortex. As astrocytes are known to occupy non-overlapping territories (Bushong et al, 2002), there may be a contact-dependent mechanism that regulates their density (Nakatsuji and Miller, 2001).…”
Section: Competition Between the Ng2 Cell-derived Astrocytes And Exismentioning
confidence: 99%
“…Especially, the accumulation of cyclin D1 results in the cyclin D-cdk4/6 complex formation, leading to a redistribution of p21 and p27 (Danen and Yamada, 2001). In addition, Nakatsuji and Miller (2001) have reported that GM3 showed no cytotoxic effects on the fibroblast, however, decreased expression of p27 was detected. In our study, WT MEFs showed the typical expression pattern of cyclin D1, p21 and p27 during their process of confluency, although GM3 KO MEFs did not show any features of cell cycle arrest (Figure 5c).…”
Section: Regulation Of Mapk and C-fos/ap-1 In Gm3 Ko Mefsmentioning
confidence: 99%
“…These cells also express p27Kip1 (Fig. 2 I), an RAregulated modulator of cell proliferation associated with neural precursors as well as astrocytes in a variety of mitotic states (Dirks et al, 1997;Legrier et al, 2001;Nakatsuji and Miller, 2001;Doetsch et al, 2002). The coincident expression of three characteristic markers (Nestin, Sox1, and Sox2) as well as an established RA-sensitive regulator of cell proliferation (p27Kip1) suggests that RA-activated cells in the SVZ are mitotically active precursors rather than recently postmitotic or differentiated neurons.…”
Section: Ra-activated Svz Cells Express General Markers Of Neural Prementioning
confidence: 99%